Implementasi Alat Pembelajaran Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VI SD Pada Materi Operasi Bilangan Bulat - Ismi Lailil Mukarromah; Putri Oktapiyani; Warsih Warsih; Yuyun Yuningsih; Yayan Alpian (Peneliti.net, 2023)
Mathematics is the basic science for the world of education because mathematics is very supportive to study other sciences. The purpose of teaching mathematics in elementary school is so that students are able to understand mathematical concepts, explain the interrelationships between concepts and apply concepts or algorithms in a flexible, accurate, efficient and precise way in solving problems of everyday life. This type of research conducted by researchers is descriptive research with a qualitative approach. Because researchers want to describe and describe more deeply about the use of props in the learning process of Mathematics. The research subjects were students of class VI SDN Wanajaya 3 in semester 1 which amounted to 15 people. The study was conducted in two cycles. For cycle I, it begins with the use of integer princes props with summation and integer materials, while in cycle II the use of integer princes props with integer reduction materials.